A facile one-pot regioselective synthesis of functionalized novel benzo[f]chromeno[4, 3-b][1, 7]naphthyridines and benzo[f][1, 7]naphthyridines via an imino Diels-Alder reaction. Issue 5 (1st February 2017) - Arepalli, Sateesh Kumar; Park, Byeongwoo; Jung, Jae-Kyung; Lee, Kiho; Lee, Heesoon
Graphical abstract: Highlights: One-pot multi-component synthetic methodology for novel scaffolds was developed. It is an atom-economy reaction affording poly-substituted napthyridine core motifs. This synthetic methodology allows broad substrate scope with intramolecular/intermolecular imino Diels-Alder reactions. We have achieved complete regioselectivity with inexpensive catalytic system. Plausible reaction mechanism has also been discussed with intramolecular imino Diels-Alder reaction by internal/external alkynes. Abstract: A novel series of functionalized 13 H -benzo[ f ]chromeno[4, 3- b ][1, 7]naphthyridines and 1, 3-diphenylbenzo[ f ][1, 7]naphthyridines have been synthesized by an efficient regioselective one-pot multicomponent synthesis through intra and intermolecular imino Diels-Alder reaction. In this method, we have achieved complete regioselectivity and atom economy with polysubstituted core motifs in moderate to good yields. The proposed mechanism of this reaction has also discussed.